Tunable bandpass filter using RF MEMS switches - Alam, A. H. M. Zahirul; Islam, Md. Rafiqul; Khan, Sheroz; Nik Mohd. Salleh, Nik Nor Atikah; Aziz, Noraini (IIUM Press, 2009)
A band pass tunable RF filter is proposed by using Radio Frequency (RF) Microelectro Mechanical Systems (MEMS). The tunability is obtained by using capacitive MEMS switches that can be tuned within the bandwidth of 3.6 GHz to 4.4 GHz. The performance of the filter depends on geometry and location and types of the MEMS switches. Optimization has been done to achieve tunability by using 3-D high frequency electromagnetic simulator (HFSS).